PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - DESRYADI RAHMATULLAH, DINI (Jurnal Akuntansi AKUNESA, 2019)
Firm value is an indicator used by investors to see the results obtained by investors when make an investment. In addition, profitability and liquidity are also used as references for investors. This study purpose to examine the effect of profitability and liquidity on firm value with capital structure as an intervening variable. The method used in this study is quantitative by collecting documentation, namely through annual reports and company finances, with a total sample of 200 companies. The analysis used in this study is to use WarpPls software. The results of this study indicate that profitability and liquidity have no influence on the value of the company on companies listed on the Indonesia Stock Exchange. Capital structure is also not able to be an intervening variable on the effect of profitability and liquidity on the value of companies listed on the Indonesia Stock Exchange.Keyword: profitability, liquidity, capital structure, firm value